2016
DOI: 10.22146/ijbiotech.9299
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Phenol-Degrading and Biofi lm-Forming Bacteria from Wastewater and Peat Soil

Abstract: Phenol is hazardous aromatic pollutant which needs to be treated to reduce its hazardous effects. Bioremediation using bacteria which can form biofi lm offer an alternative wastewater treatment that is cheaper and environmentally safe. Eighteen strains of phenol-degrading and biofi lm-forming bacteria were isolated from peat soil, also hospital and textile wastewater. Screening for phenol degradation ability of isolates were performed using Folin-ciocalteau reagent, while for biofi lm formation ability were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Use of petroleum products also cause many harms, especially many types of untreated petroleum are discharged polluting on both soil and water environment (Nandy et al, 2020). Due to its hazardous effects, it is necessary to treat oily appropriately (Khusnuryani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Use of petroleum products also cause many harms, especially many types of untreated petroleum are discharged polluting on both soil and water environment (Nandy et al, 2020). Due to its hazardous effects, it is necessary to treat oily appropriately (Khusnuryani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of bacteria to form biofilm and grow in it as a microbial consortium is considered to be an important requirement for their survival under harsh environmental conditions. Microbes growing in biofilm community can perform some complex metabolic processes Biofilm-associated bacteria embedded in a matrix of Extracellular Polymeric Substance (EPS) (Annous et al 2009), and the metabolic interaction among bacteria will enhance the degradation process (Cerca et al 2005;Andersson et al 2008;Annous et al 2009;Khusnuryani et al 2014). In this research, we examined biofilm forming ability and identified molecular characteristics of copper-resistant bacteria isolated from PT Freeport Indonesia's tailings.…”
Section: Introduc Onmentioning
confidence: 99%